Process for producing float glass from mineral materials including anhydrous sodium hydroxide

CN122892848APending Publication Date: 2026-10-09SAINT GOBAIN VITRAGE SA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580018341.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-27
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

[0092]以下是上述所有结果的总结以及本发明的优点,如根据本发明的混合物C和D的优越性能所证明的:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present invention relates to a raw material mixture for the preparation of a molten glass of float glass type having a target composition, comprising melting the raw material mixture, wherein the sodium source used is sodium hydroxide in anhydrous form, and preferably having a bulk density of less than 1.2 g / cm 3 , and more preferably less than 1.0 g / cm 3 .
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to the field of glass melting, and particularly to the production of float glass, especially float glass for the construction or automotive industries.

[0002] Glass is typically produced by melting raw materials in a furnace, including silica and at least one silica flux (such as sodium carbonate), and at least one alkaline earth metal (such as limestone (calcium carbonate) and dolomite (CaMg(CO3)2)). During melting, carbonates release carbon dioxide, and their bubbles help to agitate the molten material. Furthermore, some carbonates, such as dolomite, break into smaller particles even before releasing their CO2, according to a phenomenon called bursting, which can be quite violent and generate dust that can clog and even corrode various pipes used in the furnace (chimneys, regenerators, etc.). Eliminating bubbles in glass usually requires the addition of a clarifying agent such as sodium sulfate, whose released sulfur oxides carry residual carbon dioxide and water bubbles to the glass surface. However, sulfur oxides are particularly corrosive gases. Adding water to the glass as a clarifying agent has been proposed. In conventional soda-lime-silica glass production methods, CO2 emissions are typically around 20% of the total mass of the raw materials used. Furthermore, carbon dioxide is a greenhouse gas, and for environmental reasons, there is a desire to develop glass production methods that produce as little CO2 as possible while obtaining high-quality glass at an acceptable cost.

[0003] In addition to the CO2 released directly during the melting of the raw material bath, it is important to consider the glass production method as a whole, while taking into account other factors such as the cost of raw materials, their transportation, the energy costs associated with procuring the raw materials, and the overall energy required to melt the mixture.

[0004] As mentioned earlier, glass is typically made by melting raw materials containing a large amount of carbonates in a furnace.

[0005] During melting, carbonates release carbon dioxide, and the bubbles help to agitate the molten material. For environmental reasons, there is a desire to develop glass production methods that generate as little CO2 as possible while still producing high-quality glass at an acceptable cost, particularly in terms of the energy required to produce glass.

[0006] Sodium hydroxide has been proposed as a substitute for sodium carbonate and has the effect of reducing CO2 generated during glass manufacturing, for example, in publications US3753743A or BE761040A. Sodium hydroxide is used in the form of a caustic soda solution with a caustic soda concentration of 30 to 75% by weight.

[0007] However, as will be explained later in this specification, it becomes apparent that using a sodium hydroxide solution of such concentration significantly impairs the flowability of the vitrifiable mixture, as it becomes highly viscous due to the large amount of water added, and greatly increases the energy required for glass production. Furthermore, the chemical homogeneity of the glass is insufficient in the case of this solution.

[0008] Patent applications FR3086942 and WO2022 / 229568 also describe the use of sodium hydroxide to form soda-lime-silicon glass.

[0009] The object of the present invention is to provide a mixture for the production of soda-lime-silica glass, particularly for the production of float glass, which solves the aforementioned problems and, in particular, achieves a uniform distribution of sodium oxide and silicon oxide in the final glass, while maintaining good flowability of the vitrifiable mixture and reducing the energy consumption required for the production.

[0010] Another object of the present invention is to provide a melting method that protects the components of the melting furnace, particularly by limiting dust emissions from the furnace during melting.

[0011] To this end, the applicant's experiments demonstrated the advantages of using anhydrous sodium hydroxide as a sodium source in the initial raw material mixture, particularly when its density—and preferably its form—is particularly suitable for this application. Anhydrous form refers to any sodium hydroxide source that experiences a mass loss of less than 5% after heat treatment at 150°C for 1 hour.

[0012] More specifically, the present invention relates to a raw material mixture for preparing molten glass, the target composition of which has the following formulation, in weight percentages: - SiO2: 60 to 80%, preferably 70 to 75%, - Na2O: 5% to 20%, preferably 10% to 20%. - CaO: 5 to 20%, preferably 5 to 15%, - MgO: 0 to 10%, preferably 0.1 to 7%, - Al2O3: 0 to 10%, preferably 0.1 to 3%, - K2O: 0 to 10%, preferably 0 to 2%. - Iron oxide: 0 to 15%, preferably 0 to 10%, - B2O3: 0 to 1% (excluding), preferably less than 0.5%, - One or more other oxides: 0 to 10% cumulatively, preferably 0 to 5% cumulatively. The balance consists of unavoidable impurities.

[0013] The mixture comprises: - At least one silicon source, particularly selected from silica (especially in sand form), glass shavings, and especially mixtures of silica and glass shavings. - At least one sodium source in the form of sodium hydroxide, - At least one calcium source, preferably selected from limestone, quicklime, or hydrated lime, or a mixed oxide of calcium and at least one element selected from Si and Mg (especially calcium silicate), said calcium source may be at least partially in the form of crushed material. - Optionally, at least one magnesium source, preferably selected from dolomite (optionally calcined), magnesite (MgCO3), brucite (Mg(OH)2), or a mixed oxide of magnesium and at least one element selected from Si and Ca (especially magnesium silicate). - Optionally, at least one compound selected from the following: feldspar (especially of the formula (K,Na)AlSi3O8), nepheline or phonolite, calcined or hydrated alumina, - Optional recycling of glass scraps, - Optional slag, Sodium hydroxide is in anhydrous form.

[0014] Preferably, the mixture consists of more than 90% by weight or more than 95% by weight, and more preferably more than 99% by weight of the above-mentioned components.

[0015] Preferably, the mixture according to the invention is water-free. This means that no water is added to the mixture, and any moisture present comes from the raw materials. Preferably, based on the total weight of the mixture, the mixture contains less than 1% by weight of water, more preferably less than 0.5% by weight of water, and more preferably less than 0.2% by weight of water.

[0016] In the mixture according to the invention, sodium hydroxide is in anhydrous form, and preferably has a concentration of less than 1.2 g / cm³. 3 The bulk density is preferably less than 1.0 g / cm³. 3 or less than 0.8 g / cm 3 The bulk density.

[0017] In this specification, the term "granules" is used to describe individual entities of anhydrous sodium hydroxide.

[0018] Bulk density (or apparent density) is a commonly used quantity primarily for matter in particle (or particulate) form, used to describe the mass of the matter contained within a given volume, including the volume of void air.

[0019] Bulk density (also known as apparent density) is measured as follows: According to a reproducible procedure for measuring the apparent density of a particulate mixture, the mixture is first poured into a container (e.g., a hopper) of known mass and volume. The container should be at least 1 liter in size to ensure sufficient accuracy and to adhere to the aspect ratio limiting the compaction of the mixture by satisfying the following formula: Among them, L max V is the maximum dimension of the container in a given direction (similar to the Ferrette diameter of a particle), and V is the volume of the container.

[0020] Equally important, ensure the mixture is poured in gently without any moving of the hopper or mechanical compression of the mixture to minimize compaction. Then weigh the filled hopper to determine the mass of the poured mixture. Apparent density is the ratio between the measured mass of the mixture and the volume of the hopper.

[0021] The phrase "for preparing molten glass of the target composition" means that the various raw materials are present in the mixture in proportions suitable for ultimately melting according to the art to obtain glass of the target composition.

[0022] Therefore, the raw material mixture is intended to be heated to a certain temperature and allowed to melt to obtain glass with the target composition.

[0023] According to specific and advantageous embodiments of the invention, they can of course be combined with each other as appropriate: - The anhydrous sodium hydroxide is in the form of a particle aggregate with an average roundness of less than 0.85, preferably less than 0.80 or greater than 0.75.

[0024] - The anhydrous sodium hydroxide is in the form of a particle aggregate with an aspect ratio greater than 1.15, preferably greater than 1.20.

[0025] - The anhydrous sodium hydroxide is in the form of a particle aggregate having an average Ferrette diameter greater than 5 mm and greater than 10 mm.

[0026] - The anhydrous sodium hydroxide contains less than 30% by weight, preferably less than 25% by weight, of total water content.

[0027] - Sodium hydroxide is the only source of sodium (aside from possible additions of fragments or feldspar, nepheline or phonolite).

[0028] - Alternatively, sodium is provided in the form of a mixture of sodium hydroxide and sodium carbonate (Na2CO3), wherein the anhydrous sodium hydroxide according to the invention preferably accounts for more than 20% by weight of the mixture, or more than 50% by weight of the mixture.

[0029] - The calcium source is mineral calcium silicate, preferably natural.

[0030] - The calcium source is calcium oxide.

[0031] - The calcium source is calcium hydroxide.

[0032] - The magnesium source is the mineral magnesium silicate, preferably natural.

[0033] - The calcium source is mineral calcium silicate, preferably natural, containing more than 30% SiO2 and more than 10% CaO by weight, preferably more than 15% CaO, wherein CaO and SiO2 together account for more than 60%, or more than 70%, or more than 80% of the total weight of the source.

[0034] - The magnesium source is a mineral magnesium silicate, preferably natural, containing more than 30% SiO2 and more than 10% MgO by weight, preferably more than 15% MgO, wherein MgO and SiO2 together account for more than 60%, or more than 70% or more than 75% of the total weight of the source.

[0035] - The magnesium source is brucite Mg(OH)2.

[0036] The raw materials for the molten bath include the calcium source and the magnesium source as described above.

[0037] - The potassium source is potassium hydroxide.

[0038] Silica is usually introduced into the raw material mixture in the form of sand.

[0039] If necessary, as mentioned above, the feed mixture may also advantageously include an Al carrier, a precursor of alumina in glass, particularly derived from feldspar, hydrated or calcined alumina, or alternatively, blast furnace slag.

[0040] The raw material mixture may also contain small amounts of colorants, such as iron oxide, cobalt oxide, or chromium oxide.

[0041] According to the invention, carbonates are introduced into the raw material mixture as little as possible or not at all. Preferably, the sum of the weights of alkali metal carbonates and alkaline earth metal carbonates in the raw material mixture is less than 30%, more preferably less than 10%, more preferably less than 5%, more preferably less than 1% by weight, or even zero. According to a possible advantageous embodiment, the raw material mixture may be substantially free of any carbonates. This advantageously enables the release of only a minimal portion of carbon monoxide during heating and melting into glass, for example, due to the addition of coke to the initial mixture.

[0042] For glass production, Si support is introduced into the raw material mixture in the form of sand, while alkali metal support is advantageously introduced into the raw material mixture in the form of hydroxide, particularly anhydrous NaOH, with a particle size distribution suitable for the present invention. Aluminum support (if present) can be introduced into the raw material mixture in the form of feldspar powder.

[0043] Preferably, the raw material mixture is wetted to reduce the dispersion of fine particles, and the final total moisture content of the mixture is preferably less than 4.5%, more preferably less than 3.5%, and even more preferably less than 3%.

[0044] Each raw material is introduced into the raw material mixture in such an amount that the molar percentage of its cation (such as Si, Na, Al, Fe, etc.) relative to the total moles of all cations is the same as its molar percentage in the final glass. As described above, the raw materials in the mixture are selected to produce a glass with a target composition falling within the aforementioned range (the percentage range of various oxides).

[0045] Heating a mixture of raw materials to obtain molten glass is typically carried out in a furnace. The temperature and duration of heating are adjusted according to the desired quality of the glass, particularly based on tolerance for unmelted particles (called "stones," or "infondus") and bubbles. Typically, the maximum heating temperature for molten glass is between 1200 and 1700°C. Glass melting techniques well known to those skilled in the art can be used to convert raw material mixtures into glass. This conversion can be carried out in any type of furnace, such as an electric furnace with electrodes, a top-fired furnace (e.g., a cross-flame furnace or annular flame furnace), or a submerged combustion furnace.

[0046] To be heated and melted into glass, the raw material mixture can be introduced into the furnace in powder form, meaning that each raw material it contains is in powder form. Alternatively, to be heated and melted into glass, the raw material mixture can be introduced into the furnace as a composition comprising scrap and the raw material mixture, the mixture optionally being in powder form.

[0047] The present invention also relates to a method for producing glass having the same objective composition, comprising melting a mixture of raw materials according to any one of the preceding claims, the mixture constituting a melt bath, the method comprising the following steps: a) Selecting the required amount of the raw material to obtain glass having the target composition after melting, wherein the raw material is selected from at least the following: - At least one silicon source, particularly selected from silicon dioxide, especially in the form of sand, glass shards, and especially mixtures of silicon dioxide and glass shards. - At least one sodium source in the form of sodium hydroxide, - At least one calcium source, preferably selected from limestone, quicklime, or hydrated lime, or a mixed oxide of calcium and at least one element selected from Si and Mg (especially calcium silicate), said calcium source may be at least partially in the form of crushed material. - Optionally, at least one magnesium source, preferably selected from dolomite (optionally calcined), magnesite (MgCO3), brucite (Mg(OH)2), or a mixed oxide of magnesium and at least one element selected from Si and Ca (especially magnesium silicate). - Optionally, at least one compound selected from the following: feldspar (especially of the formula (K,Na)AlSi3O8), nepheline or phonolite, calcined or hydrated alumina, - Optional recycling of glass scraps, - Optional slag, b) Prepare the mixture of the raw materials according to the stated amount. c) Melt and cool the mixture under conditions that allow for the production of the glass. The sodium hydroxide in the mixture is in anhydrous form.

[0048] Preferably, the bulk density of sodium hydroxide is less than 1.2 g / cm³. 3 More preferably, the bulk density is less than 1.0 g / cm³. 3 . Example

[0049] In the following examples, different raw material mixtures were prepared to compare with mixtures currently used in glass production for the same final glass composition, which essentially have the following composition: [Table 1] .

[0050] Table 2 below shows the proportions of various raw materials in the five mixtures prepared: [Table 2] .

[0051] The mixtures differ in bulk density and morphology of the sodium hydroxide source used.

[0052] The geometric characteristics of the various sodium hydroxide forms used were determined using image analysis with ImageJ® software. The median diameter, Ferrette diameter, roundness, and aspect ratio were thus determined for each sodium hydroxide, and their values ​​are listed in Table 3 below.

[0053] And more specifically: The roundness of the particles is determined by the formula S = 4π(A / P). 2 The area is given by , where A is the area and P is the perimeter of the particle.

[0054] The Freette diameter is conventionally defined as the distance between two parallel tangents that are tangent to the periphery of the particle's projected surface in one direction.

[0055] Median diameter d for each sodium hydroxide sample50 Image analysis measurements were also performed using ImageJ® software.

[0056] The equivalent diameter of a particle is defined as the diameter of a circle whose circumference is equivalent to that of the particle (as measured in the image).

[0057] The aspect ratio of a particle is the ratio of its longest length to its shortest length.

[0058] Then, the average roundness, Freret diameter, equivalent diameter, and aspect ratio of the particle set for each sodium hydroxide sample were defined, as shown in Table 3 below.

[0059] The report also detailed the ratio of free water to bound water in these different grades of sodium hydroxide.

[0060] Typically, the median diameter is the diameter of 50% of the particles (by number) that is smaller than that diameter and the diameter of 50% of the particles that is larger than that diameter.

[0061] [Table 3] Total water corresponds to free water plus bound water.

[0062] Therefore, the percentage of bound water is obtained by subtracting the percentage of free water from the total percentage of water (the “Balance” in Table 3 above).

[0063] Bound water refers to water chemically bonded to a structure through strong bonds, typically represented by the hydroxyl group -OH in the general formula of NaOH. The removal (dehydroxylation) of bound water occurs at temperatures well above 100°C. In the case of dehydroxylation with anhydrous sodium hydroxide, free water is essentially bound water according to the formula 2NaOH → Na₂O + H₂O.

[0064] "Anhydrous form" specifically refers to any sodium hydroxide source that results in a mass loss of less than 5%, preferably less than 2%, after heat treatment at 150°C for 1 hour.

[0065] On the other hand, "free water" refers to all water molecules bound together by weak interactions. Free water can, for example, correspond to water in a solution containing sodium hydroxide, as described in US3753743A, but also to water present between sodium hydroxide particles, particularly due to the hygroscopic nature of the compound. Unlike bound water, this water is weakly bonded to sodium hydroxide via weak bonds.

[0066] Therefore, "anhydrous" sodium hydroxide contains less than 5% free water, and preferably less than 2% free water, as previously stated.

[0067] For the purposes of this invention, sodium hydroxide containing less than 5% free water is referred to as anhydrous.

[0068] Mixture B conforms to the teachings of US3753743A. Mixtures C and D are consistent with the objectives of this invention. Example A is a comparative example, in which sodium carbonate is conventionally used as the sodium source.

[0069] The properties and quality of the raw material mixtures in Examples A to D above, including the quality of the molten glass, are measured according to the following standards: 1°) Flow measurement using the angle of repose test Angle of repose is a method for evaluating powder flowability and is used to predict the flow of vitrifiable mixtures from the mixer to the furnace.

[0070] This technique allows for the estimation of the flow patterns of other vitrifiable mixtures relative to a reference mixture (mixture A). If the flow is weak or poor, the risk of blockage in the conveyor belt or furnace hopper is greater.

[0071] Regarding the angle of repose, the vitrifiable mixture is fed into a hopper with a gate. The gate is then removed to allow the vitrifiable mixture to flow onto graph paper, forming a cone. The height of the cone is measured, and its circumference is plotted on the graph paper to derive its average diameter. Finally, combining the cone height and diameter, the angle of repose of the vitrifiable mixture is calculated using the following formula: Angle of repose (degrees) = 180 × arctan(height / (1 / 2 × cone diameter)) / π. The measurement results are interpreted according to the classification given in "Technique de l'ingénieur – Mise en forme des solides" [Engineering Technique – Solid Forming]. Ref J3380 V1.

[0072] The results are compiled in Table 4 below.

[0073] The reference mixture (mixture A) exhibits very good flow properties, as do mixtures C and D, with an angle of repose between 25 and 30° (see the classification in Engineering Technique - Solid Forming. Ref J3380 V1). Mixture D has good flow properties with an angle of repose of 32°. On the other hand, mixture B, with an angle of repose greater than 50°, has poor flow properties and is predicted to require, for example, the use of suitable devices to assist in unloading when the mixture passes through the hopper. Furthermore, when using mixture B, there is a high risk of clogging the mixer or the conveyor belt.

[0074] Mixtures B, C, and D were characterized, and the results are shown in Table 4 below. Mixtures C and D according to the invention, and especially Example C, can be considered to be the most free-flowing.

[0075] [Table 4] .

[0076] 2°) Emissivity Measurement Low emissivity raw material mixtures generate a thermal barrier on the surface of the composite material pile, which slows down the melting rate and increases the furnace energy consumption to achieve the same degree of melting.

[0077] The emissivity of the various mixtures shown in Table 5 below was measured from the reflectance spectrum using the law of conservation of energy for opaque materials: absorptivity α(λ,T) + reflectivity ρ(λ,T) = 1. By applying Kirchhoff's laws, the spectral emissivity can be expressed as the total reflectance. ε(λ,T) = α(λ,T) in: , Among them B T The spectral irradiance of the blackbody at a temperature T of 2000°C (corresponding to the temperature of the air-gas flame in the burner).

[0078] At room temperature, hemispherical reflectance was measured between 300 and 2500 nm using a 150 mm integrating sphere mounted on a Lambda spectrophotometer, with a Spectralon plate used as a reflectance reference.

[0079] For ease of handling, vitrifiable mixture samples are prepared by applying 0.4 tons / cm². 2 Apply pressure and moisten with 2% water before measurement.

[0080] [Table 5] .

[0081] To improve heat transfer between the flame and the glass, those skilled in the art seek to maximize the emissivity of the batch as much as possible. If the emissivity is too low, a sign of high thermal reflectivity, it can lead to a shielding effect. This will increase the temperature at the furnace top and decrease the temperature of the glass bath. The data in Table 5 show that, according to Examples C and D, the use of anhydrous sodium hydroxide improved the heat absorption of the batch compared to the use of sodium carbonate (mixture A).

[0082] 3°) Energy required for melting The reduction in energy consumption logically leads to lower costs (less energy is required to melt the raw material mixture) and a lower carbon footprint in glass production (e.g., less gas is used).

[0083] The energy required to melt mixtures of different raw materials was determined using FactSage 8.0 software. The energy was calculated over a temperature range of 25 to 1400°C.

[0084] The evaluation results are reported in Table 6 below: [Table 6] .

[0085] Table 6 shows that using mixture B (50% free water), the melting energy of the vitrifiable mixture increases dramatically: by 23% compared to the reference (mixture A). On the other hand, when using other mixtures C and D according to the invention, energy consumption is significantly reduced by about 11% relative to the same reference.

[0086] 4°) Homogeneity of the glass obtained after melting Inhomogeneous glass exhibits "ribs" (optical defects), which are regions where the refractive index varies locally due to changes in chemical composition.

[0087] The mixtures listed in Table 2 were used to melt glass samples in cylindrical platinum crucibles. Each sample was heated in air at 1480°C for 2 hours. The cooled glass was then cored and cut to obtain glass slides containing cylindrical cross-sections. The glass slides were polished, carbon-coated, and analyzed using a 15 kV electron probe microanalysis. The analysis included determining the mass percentages of Na₂O, CaO, and SiO₂ at 50 measurement points in 500-micron measurement steps along the height of the glass slide (or molten sample).

[0088] The average concentrations and standard deviations of Na₂O, CaO, and SiO₂ can be calculated from this. The homogeneity standards of Na₂O, CaO, and SiO₂ in glass are provided by the ratios of the standard deviations to the average concentrations (σNa₂O / [Na₂O], σCaO / [CaO], and σSiO₂ / [SiO₂]).

[0089] The results are reported in Table 7 below.

[0090] [Table 7] .

[0091] In the case of mixtures C and D according to the invention, and more particularly in the case of mixture C according to the invention, the uniformity of sodium oxide and silicon oxide appears to be particularly improved.

[0092] The following is a summary of all the above results and the advantages of the invention, as demonstrated by the superior performance of mixtures C and D according to the invention: - Good flowability of the raw material mixture, - Improved emissivity of vitrifiable mixtures, which implies better heat transfer from the flame to the feed mixture during melting. - A significant reduction in the total melting energy of the mixture. - Better uniformity in the final glass.

Claims

1. A raw material mixture for producing glass having the following composition: - SiO2: 60 to 80%, preferably 70 to 75%, - Na2O: 5% to 20%, preferably 10% to 20%. - CaO: 5 to 20%, preferably 5 to 15%, - MgO: 0 to 10%, preferably 0.1 to 7%, - Al2O3: 0 to 10%, preferably 0.1 to 3%, - K2O: 0 to 10%, preferably 0 to 2%. - Iron oxide: 0 to 15%, preferably 0 to 10%, - B2O3: 0 to 1% (excluding), preferably less than 0.5%, One or more other oxides: 0 to 10% cumulatively, preferably 0 to 5% cumulatively. The balance consists of unavoidable impurities. The mixture comprises: - At least one silicon source, particularly selected from silicon dioxide, especially in the form of sand, glass shards, and especially mixtures of silicon dioxide and glass shards. - At least one sodium source in the form of sodium hydroxide, - At least one calcium source, preferably selected from limestone, quicklime, or hydrated lime, or a mixed oxide of calcium and at least one element selected from Si and Mg, particularly calcium silicate, wherein the calcium source may be at least partially in the form of crushed material. - Optionally, at least one magnesium source, preferably selected from dolomite, optionally calcined, magnesite, or a mixed oxide of magnesium and at least one element selected from Si and Ca, particularly magnesium silicate. - Optionally, at least one compound selected from the following: feldspar, particularly of the formula (K,Na)AlSi3O8, nepheline or phonolite, calcined or hydrated alumina, - Optional slag, - Optional recycling of glass scraps, Its features The sodium hydroxide is in anhydrous form.

2. The mixture according to claim 1, wherein the anhydrous sodium hydroxide has a concentration of less than 1.2 g / cm³. 3 The bulk density.

3. The mixture according to claim 1 or 2, wherein the anhydrous sodium hydroxide is in the form of a collection of particles having an average sphericity of less than or equal to 0.85, preferably less than 0.80 or less than 0.

75.

4. The mixture according to any one of the preceding claims, wherein the anhydrous sodium hydroxide is in the form of a particle aggregate having an aspect ratio greater than 1.15, preferably greater than 1.

20.

5. The mixture according to any one of the preceding claims, wherein the anhydrous sodium hydroxide is in the form of a collection of particles having an average Ferrette diameter greater than 5 mm, preferably greater than 10 mm.

6. The mixture according to any one of the preceding claims, wherein the anhydrous sodium hydroxide comprises less than 30% by weight, preferably less than 25% by weight, of total water.

7. The mixture according to any one of the preceding claims, wherein the anhydrous sodium hydroxide is the sole source of sodium, in addition to possible additions of crushed material or feldspar, nepheline or phonolite.

8. The mixture according to any one of the preceding claims, wherein the sodium is provided in the form of a mixture of anhydrous sodium hydroxide and sodium carbonate Na2CO3, wherein the anhydrous sodium hydroxide preferably accounts for more than 20% by weight of the mixture, or more than 50% by weight of the mixture.

9. The mixture according to any one of the preceding claims, wherein the calcium source is mineral calcium silicate, comprising more than 30% SiO2 and more than 10% CaO by weight percentage, preferably more than 15% CaO, wherein CaO and SiO2 together account for more than 60%, or more than 70%, or more than 80% of the total weight of the source.

10. The mixture according to any one of the preceding claims, wherein the magnesium source is magnesium silicate mineral, comprising more than 30% SiO2 and more than 10% MgO by weight percentage, preferably more than 15% MgO, wherein MgO and SiO2 together account for more than 60%, or more than 70% or more than 75% of the total weight of the source.

11. The mixture according to any one of the preceding claims, wherein the potassium source is potassium hydroxide.

12. The mixture according to any one of the preceding claims, wherein the calcium source is calcium hydroxide.

13. The mixture according to any one of the preceding claims, wherein the magnesium source is magnesium hydroxide.

14. The mixture according to any one of the preceding claims, wherein the anhydrous sodium hydroxide has a concentration of less than 1.0 g / cm³. 3 Preferably less than 0.8 g / cm³ 3 The bulk density.

15. A method for producing glass having a target composition, comprising melting a raw material mixture according to any one of the preceding claims, the mixture constituting a melt bath, the target composition satisfying the following criteria, in weight percentage: - SiO2: 60 to 80%, preferably 70 to 75%, - Na2O: 5% to 20%, preferably 10% to 20%. - CaO: 5 to 20%, preferably 5 to 15%, - MgO: 0 to 10%, preferably 0.1 to 7%, - Al2O3: 0 to 10%, preferably 0.1 to 3%, - K2O: 0 to 10%, preferably 0 to 2%. - Iron oxide: 0 to 15%, preferably 0 to 10%, - B2O3: 0 to 1% (excluding), preferably less than 0.5%, One or more other oxides: 0 to 10% cumulatively, preferably 0 to 5%, with the balance consisting of unavoidable impurities. The method is characterized by comprising the following steps: a) Selecting the required amount of the raw material to obtain glass having the target composition after melting, wherein the raw material of the molten bath is selected from at least the following: - At least one silicon source, particularly selected from silicon dioxide, especially in the form of sand, glass shards, and especially mixtures of silicon dioxide and glass shards. - At least one sodium source in the form of sodium hydroxide, - At least one calcium source, preferably selected from limestone, quicklime, or hydrated lime, or a mixed oxide of calcium and at least one element selected from Si and Mg, particularly calcium silicate, wherein the calcium source may be at least partially in the form of crushed material. - Optionally, at least one magnesium source, preferably selected from dolomite, optionally calcined, magnesite, or a mixed oxide of magnesium and at least one element selected from Si and Ca, particularly magnesium silicate. - Optionally at least one compound selected from the following: feldspar, particularly having the formula (K,Na)AlSi3O8, nepheline or phonolite, calcined or hydrated alumina, - Optional recycling of glass scraps, - Optional slag, b) Prepare the mixture of the raw materials according to the stated amount. c) Melt and cool the mixture under conditions that allow for the production of the glass. The sodium hydroxide in the mixture is in anhydrous form.

16. The production method according to the preceding claim, wherein the anhydrous sodium hydroxide has a concentration of less than 1.2 g / cm³. 3 Preferably less than 1.0 g / cm³ 3 The bulk density.

Citation Information

Patent Citations

  • PROCESS FOR MANUFACTURING THIN GLASS IN A NEARLY INSTANT MANNER

    BE761040A

  • Method for preparing glass batch

    US3753743A

  • Method for producing float glass from unprocessed mineral materials

    WO2022229568A1